PENGGILINGAN DAN PEMASARAN BAHAN JAMU TRADISIONAL DI KABUPATEN SUKOHARJO - Sudarmi Sudarmi; Maria Helena Sri Rahayu (LPPM UNS, 2015)
The purpose of community service on Small and Medium Enterprises (SME) Milling and Marketing bussines of Traditional Medicinal Materials in Sukoharjo are: 1) Increasing knowledge about hygiene in working with medicinal products. 2) Increased capacity and management skills such as bookkeeping and packaging capabilities. 3) Increasing the effectiveness of the production, by using the appropriate machine tool. Indicators of success in science and technology applied to